2016
DOI: 10.1093/nar/gkw105
|View full text |Cite
|
Sign up to set email alerts
|

A phospho-dependent mechanism involving NCoR and KMT2D controls a permissive chromatin state at Notch target genes

Abstract: The transcriptional shift from repression to activation of target genes is crucial for the fidelity of Notch responses through incompletely understood mechanisms that likely involve chromatin-based control. To activate silenced genes, repressive chromatin marks are removed and active marks must be acquired. Histone H3 lysine-4 (H3K4) demethylases are key chromatin modifiers that establish the repressive chromatin state at Notch target genes. However, the counteracting histone methyltransferase required for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 59 publications
6
121
2
1
Order By: Relevance
“…Rbpj is the major transcriptional effector of Notch signaling (64). Recent studies in Drosophila demonstrated that KMT2D binds nuclear Notch co-activator complex (65), establishing a strong precedent of a regulatory link between Notch pathway and KMT2D (66). This report is consistent with our findings that loss of kmt2d produces a misbalance of Notch signaling at the level of transcription factor regulation.…”
Section: Discussionsupporting
confidence: 91%
“…Rbpj is the major transcriptional effector of Notch signaling (64). Recent studies in Drosophila demonstrated that KMT2D binds nuclear Notch co-activator complex (65), establishing a strong precedent of a regulatory link between Notch pathway and KMT2D (66). This report is consistent with our findings that loss of kmt2d produces a misbalance of Notch signaling at the level of transcription factor regulation.…”
Section: Discussionsupporting
confidence: 91%
“…The investigators found that NCor does not bind to Mint/SHARP/SPEN unless it is phosphorylated by CKII on a conserved LSDSD motif; once phosphorylated, NCor effectively compete with Kmt2D for Mint/SHARP/SPEN binding. The recruitment of NCor represses transcription whereas the recruitment of the MLL4 complex to RBPj-bound regions enhances the retention of transcription-ready chromatin (Oswald et al, 2016), reminiscent of reports that Mint enhanced transcription mediated by Runx2 (Sierra et al, 2004). …”
Section: ) Free At Last: the Latest Insights On Nicd Function In Thementioning
confidence: 89%
“…A recent study explored the Mint/SHARP/SPEN repression complex in some detail and reported a surprising observation (Figure 2C,D; (Oswald et al, 2016)). The C-terminal SPOC domain of the Mint/SHARP/SPEN protein bound to the MLL4 activator complex via Kmt2D, a H3K4 methyltransferase that generates H3K4me3 marks.…”
Section: ) Free At Last: the Latest Insights On Nicd Function In Thementioning
confidence: 93%
“…These residues are required for the SPOC-containing protein SHARP to interact with the co-repressor complex SMRT/NCoR (Ariyoshi and Schwabe, 2003). Serine phosphorylation of the LSD motif within SMRT or NCoR increases their binding affinity for the conserved Arg within the SHARP SPOC domain, suggesting that the SPOC domain is a phospho-serine binding module (Mikami et al, 2014;Oswald et al, 2016).…”
Section: Phf3 Spoc Preferentially Binds Rna Pol II Ctd Phosphorylatedmentioning
confidence: 99%